Cyber Parenting In Society 5.0 - Emilia Mude (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
The family is the first educational environment for children, because in this environment the child first gets education and guidance from both parents. Education in the family does not have the curriculum as usual as in schools in general, the family environment is believed to be a strong foundation for children's education, because children are born and raised in the family environment. Therefore, it is a good time to instill the values ​​of character, character, and good behavior from parents to their children. Thus it is clear that the first and foremost person responsible (parenting) for the survival and education of children is the parent. The family environment must give full role to the development of the family to provide a comprehensive and sustainable education system. Parents (parents) must provide for both biological and psycholytic needs for their children, and educate and guide in religious spiritual life so that children become resilient and can live in the midst of society. There are still parents who only understand part of the responsibility for raising children in the family. Therefore, it is very important for parents to understand and have the principles or the right way to educate and guide and raise children in the family in the middle of the Information Technology Gereration 5.0 community that is